Acute toxicity of organophosphorous pesticide diazinon and its effects on behavior and some hematological parameters of fingerling European catfish (Silurus glanis L.) - Koprucu, Sibel Simsek; Koprucu, Kenan; Ural, Mevlut Sener; Ispir, Unal; Pala, Murat (Academic Press Inc Elsevier Science, 2006)
Diazinon is commonly used for pest control in the agricultural fields surrounding freshwater reservoirs. So this study was conducted to determine the acute toxicity of this organophosphorous pesticide, contaminating aquatic ecosystems as a pollutant, and its effects on behavior, and some hematological parameters of fingerling European catfish, Silurus glanis. Diazinon was applied at concentrations of 1, 2, 4, 8, 16, 32, and 64 mg L-1. The water temperature in the experimental units was kept at 16 +/- 1 degrees C. The number of dead fishes significantly increased in response to diazinon concentrations 2-64 mg L-1 (p < 0.05). With increasing diazinon concentrations, the fishes exposed duration 1-96 h significantly increased the number of dead fishes (p < 0.05 for each cases). The 1, 24, 48, 72, and 96 h LC50 values (with 95% confidence limits) of diazinon for fingerling European catfish were estimated as 14.597 (12.985-16.340), 12.487 (11.079-14.471), 8.932 (7.907-10.348), 6.326 (no data because of p > 0.05), and 4.142 (no data because of p > 0.05) mg L-1, respectively. Compared to the control specimens, fish after an acute exposure to diazinon was significantly lower erythrocyte, leukocyte, hemoglobin, hematocrit, MCV, MCH, and MCHC values (p < 0.05). In addition, it was also showed a significantly negative correlation between these hematological parameters and exposure times of diazinon (p < 0.01). (c) 2006 Elsevier Inc. All rights reserved.
Keywords: European catfish; Silurus glanis; organophosphorous pesticide; diazinon; acute toxicity; behavior; hematological parameters